Case Report: Trapdoor procedure combined with arthrodiastasis treating chondroblastoma of the femoral head in adolescents - Xie, Yuyin; Liu, Can; Chen, Yifan; Yi, Yangfei; Tang, Zhongwen; Wen, Jie; Xiao, Sheng (Frontiers in Pediatrics, 2025)
Chondroblastoma is a rare benign bone tumor that typically arises in the epiphysis. The primary treatment strategy involves complete curettage of the lesion. However, there is limited literature regarding the management of chondroblastoma specifically located in the femoral head. Following simple curettage alone, the femoral head is prone to collapse due to injury to the growth plate and the effects of weight-bearing stress. Arthrodiastasis can provide a conducive environment for healing and remodeling of the necrotic or grafted femoral head by maintaining continuous distraction of the hip joint space and reducing mechanical pressure. Analogous to the use of skeletal traction in fracture management, sustained arthrodiastasis can effectively counteract compressive forces exerted by muscular contraction on the femoral head. We present the case of a 15-year-old patient with a chondroblastoma localized in the right femoral head who demonstrated favorable clinical and radiographic outcomes following Trapdoor procedure combined with Arthrodiastasis treatment.